2005
DOI: 10.1007/s11103-005-3098-x
|View full text |Cite
|
Sign up to set email alerts
|

Translation initiation factors eIF4E and eIFiso4E are required for polysome formation and regulate plant growth in tobacco

Abstract: eIF4E and eIFiso4E T AbstractEukaryotic initiation factor eIF4E plays a pivotal role in translation initiation. As a component of the ternary eIF4F complex, eIF4E interacts with the mRNA cap structure to facilitate recruitment of the 40S ribosomal subunit onto mRNA. Plants contain two distinct cap-binding proteins, eIF4E and eIFiso4E, that assemble into different eIF4F complexes. To study the functional roles of eIF4E and eIFiso4E in tobacco, we isolated two corresponding cDNAs, NteIF4E1 and NteIFiso4E1, and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…Most importantly, plants possess two quite distinct protein complexes for 5' cap recognition, a classical eIF4F, and a smaller yet more abundant eIFiso4F. Depletion of both eIF4E and eIFiso4E in tobacco with RNA interference results in semi-dwarf phenotypes and reduces polyribosome loading overall (Combe et al, 2005). The reduction in plant growth and development may be attributable to an overall reduction in protein synthesis.…”
Section: Aspects Of Translation Unique To Plantsmentioning
confidence: 99%
“…Most importantly, plants possess two quite distinct protein complexes for 5' cap recognition, a classical eIF4F, and a smaller yet more abundant eIFiso4F. Depletion of both eIF4E and eIFiso4E in tobacco with RNA interference results in semi-dwarf phenotypes and reduces polyribosome loading overall (Combe et al, 2005). The reduction in plant growth and development may be attributable to an overall reduction in protein synthesis.…”
Section: Aspects Of Translation Unique To Plantsmentioning
confidence: 99%
“…33 To examine whether they also contained other transcripts, RT-PCR analysis was performed. Several tobacco pollen-specific genes were tested including profilin, 39 actin depolymerizing factor 1 (ADF1), 40 eukaryotic translation initiation factors eIF4E, eIFiso4E 41 and R-tubulin A1 (accession number AJ421411; D. Brevario, direct submission). RT-PCR analysis revealed that all tested transcripts were present in the EPP fractions isolated by ultracentrifugation as well as directly from SEC ( Figure 3).…”
Section: Epps Contain Different Mrnasmentioning
confidence: 99%
“…However, an eifiso4g1 eifiso4g2 double mutant displays pleiotropic developmental defaults including dwarfism and reduced fertility 5 . Likewise, silencing of several eIF4E genes in Nicotiana tabacum or Lycopersicon esculentum led to dwarf plants 11 , 12 …”
mentioning
confidence: 99%